1991
DOI: 10.1128/jb.173.18.5604-5611.1991
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic DNA repair in enterobacteria

Abstract: Sixteen species of enterobacteria have been screened for mutagenic DNA repair activity. In Escherichia coli, mutagenic DNA repair is encoded by the umuDC operon. Synthesis of UmuD and UmuC proteins is induced as part of the SOS response to DNA damage, and after induction, the UmuD protein undergoes an autocatalytic cleavage to produce the carboxy-terminal UmuD' fragment needed for induced mutagenesis. The presence of a similar system in other species was examined by using a combined approach of inducible-mutag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 51 publications
0
26
0
1
Order By: Relevance
“…D. radiodurans, for example, has very effective repair of UV lesions but lacks an error-prone form of repair and is not mutated by even lethal doses of UV (23). Indeed, even the phylogenetically close relatives within the enteric bacteria differ by factors of up to 200 in their ability to be mutated by UV (29). E. coli, used here as a control strain, is the most UV-mutable species of this group (29), yet its error-prone repair makes little contribution in wild-type cells to the overall survival of UV radiation (32,34).…”
Section: Discussionmentioning
confidence: 99%
“…D. radiodurans, for example, has very effective repair of UV lesions but lacks an error-prone form of repair and is not mutated by even lethal doses of UV (23). Indeed, even the phylogenetically close relatives within the enteric bacteria differ by factors of up to 200 in their ability to be mutated by UV (29). E. coli, used here as a control strain, is the most UV-mutable species of this group (29), yet its error-prone repair makes little contribution in wild-type cells to the overall survival of UV radiation (32,34).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the lack of an obvious evolutionary selection for proteins that promote mutagenesis and the fact that there are several bacterial species that contain umuDC homologs but are not mutable by UV (41), it has been previously suggested VOL. 178, 1996 UmuDC-MEDIATED COLD SENSITIVITY 4409…”
Section: Figmentioning
confidence: 99%
“…These mutagenesis proteins are induced as part of the cellular SOS response to DNA damage. Over the past few years, molecular and genetic studies have revealed umu-like genes and proteins in a number of bacterial strains (27,45). Interestingly, these mutagenic DNA repair genes appear to reside in two locations: either chromosomally, such as the umuDC genes from Eschenichia coli and Salmonella typhimurium (20,37,49,53), or on certain naturally occurring plasmids, such as the mucAB, impCAB, and samAB operons (23,30,37).…”
mentioning
confidence: 99%